Characteristics and outcomes of patients with multiple myeloma aged 21-40 years versus 41-60 years: a multi-institutional case-control study - Jurczyszyn, Artur; Nahi, Hareth; Avivi, Irit; Gozzetti, Alessandro; Niesvizky, Ruben; Yadlapati, Sujitha; Jayabalan, David S; Robak, Paweł; Pika, Tomas; Andersen, Kristian T; Rasche, Leo; Mądry, Krzysztof; et al. (British journal of haematology, 2016)
We compared the outcomes of multiple myeloma (MM) patients aged 21-40 and 41-60 years in the novel agent era. This case-control study included 1089 patients between 2000 and 2015. Cases and controls were matched for sex, International Staging System (ISS) stage and institution. There were 173 patients in the younger group and 916 patients in the older group. Younger patients presented with a higher incidence of lytic lesions (82% vs. 72%; P = 0·04) and high-risk cytogenetic abnormalities (83% vs. 68%; P = 0·007), but lower rate of elevated lactate dehydrogenase (21% vs. 44%; P < 0·001). Five- and 10-year overall survival (OS) in younger versus older patients was 83% vs. 67% and 56% vs. 39%, respectively (P < 0·001). Similar results were seen when studying the subset of 780 patients who underwent autologous transplantation. Younger patients with ISS stage 1 had a better OS than older patients (P < 0·001). There was no survival difference between younger and older patients with ISS stage 2 or 3. Younger MM patients, aged 21-40 years, treated in the era of novel agents have a better OS than their counterparts aged 41-60 years, but the survival advantage observed in younger patients was lost in more advanced stages of MM.
Keywords: transplantation; Multiple Myeloma; Male; survival; výsledek terapie; Middle Aged; mužské pohlaví; studie případů a kontrol; L-laktátdehydrogenasa; míra přežití; Adult; mladý dospělý; young; věkové faktory; myeloma; Hematopoietic Stem Cell Transplantation; Neoplasm Staging; mnohočetný myelom; Young Adult; Transplantation, Autologous; ženské pohlaví; transplantace hematopoetických kmenových buněk; Humans; L-Lactate Dehydrogenase; Survival Rate; Chromosome Aberrations; lidé středního věku; chromozomální aberace; Age Factors; staging nádorů; autologní transplantace; dospělí; outcomes; Female; Treatment Outcome; lidé; Case-Control Studies